2016
DOI: 10.1111/ijpo.12113
|View full text |Cite
|
Sign up to set email alerts
|

Validation of obesity susceptibility loci identified by genome‐wide association studies in early childhood in South Brazilian children

Abstract: Our results indicate that genetic variants in/near these genes contribute to obesity susceptibility in childhood and highlight the age at which they begin to affect obesity-related phenotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 30 publications
4
24
0
2
Order By: Relevance
“…To date, GWA analyses have identified more than thirty susceptibility loci robustly associated with obesity measured by body mass index (BMI). Those loci are in or near genes, including GNPDA2, SH2B1, TMEM18, MTCH2, CDKAL1, FAIM2, and MC4R [5][6][7][8]. It has been reported that the genotype-phenotype association varies in diverse groups of patients, and results need to be verified in a specific population [9].…”
Section: Introductionmentioning
confidence: 99%
“…To date, GWA analyses have identified more than thirty susceptibility loci robustly associated with obesity measured by body mass index (BMI). Those loci are in or near genes, including GNPDA2, SH2B1, TMEM18, MTCH2, CDKAL1, FAIM2, and MC4R [5][6][7][8]. It has been reported that the genotype-phenotype association varies in diverse groups of patients, and results need to be verified in a specific population [9].…”
Section: Introductionmentioning
confidence: 99%
“…Ideally, these studies would be designed with repeated use of validated tools throughout early childhood to assess eating behaviour or energy intake and conducted in populations with higher prevalence of overweight. As previous studies have shown that these BMI variants could be relevant also to other non‐Caucasian populations, it would be interesting to conduct similar analyses in non‐Caucasian populations.…”
Section: Discussionmentioning
confidence: 96%
“…SEC16B proteins, which are expressed ubiquitously in various tissues, may have a role in regulating the secretion of appetite‐related peptides, such as orexin, neuropeptide Y, and proopiomelanocortin . The function of Sec16 has not been clearly proven; however, Sec16 has been hypothesized to be a possible factor involved in the regulation of food intake, especially increased energy, carbohydrate, and lipid intake, and thus, alterations in the levels or function of Sec16 could be related to the development of obesity. Furthermore, some GWASs identified that rs591120 in SEC16B is associated with the obesity phenotype, which is consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%